Pengaruh Kualitas Pelayanan, Sarana Prasarana dan Promosi dalam Meningkatkan Minat Baca di Perpustakaan Al-Hikam - Moh Ulil Ampri; Eka Farida; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study was to determine the effect of service quality, infrastructure and promotion on increasing reading interest. The research used is a quantitative method. The population in this study were the students of the Al-Hikam Malang Islamic boarding school as many as 356 students. While the samples used in this study were 78 samples. The data used is primary data using a questionnaire. The data analysis method used is instrument test: validity and reliability test, normality test, classic assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination. From the results of the study simultaneously obtained results that service quality, infrastructure and promotion have a significant effect on reading interest, service quality variable has a positive effect on reading interest, infrastructure variable has no significant positive effect on reading interest and promotion variable has no significant positive effect on reading interest . positive but not significant effect on reading interest Keywords: Quality of Service, Infrastructure, Promotion, Interest in Reading